Rapid and simple method for preparation of genomic DNA from easily obtainable clotted blood. - Kanai, N (1994)
A method was developed for the preparation of genomic DNA from clotted blood that is usually discarded after extraction, for other laboratory tests. The method, which involves proteinase K digestion, salt/chloroform extraction and 90% ethanol precipitation of DNA from clotted blood, is rapid, simple, and easy because it does not impose an extra burden on the patient.